Determinants of Fraud Prevention in Village Fund Management with Organizational Justice as Moderator - Murtanto, Murtanto; Banjarnahor, Erliana; Ferisanti, Ferisanti (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
This study aims to obtain empirical evidence about the effect of fraud prevention factors on village fund management. It also examines the role of organizational justice as a moderating variable through an associative study method. The population used consists of 120 respondents from the Village Government Apparatus in Muaragembong District, Bekasi Regency, West Java Province, Indonesia. Furthermore, the data were collected using the SPSS version 22 application program to analyze the effect of the internal control system, organizational commitment, leadership style, and HR competence on fraud prevention. The results showed that the Internal Control System, organizational commitment, leadership style, and HR competence significantly affect fraud prevention in village fund management. Meanwhile, organizational justice strengthens the positive effect of commitment on fraud prevention but not on the Internal Control System, leadership style, and HR competence.